Complete Genome Sequence of KPC-Producing Klebsiella pneumoniae Strain CAV1193. - Sheppard, A; Stoesser, N; Sebra, R; Kasarskis, A; Deikus, G; Anson, L; Walker, A; Peto, T; Crook, D; Mathers, A (American Society for Microbiology, 2016)
Carbapenem resistance in Klebsiella pneumoniae, frequently conferred by the blaKPC gene, is a major public health threat. We sequenced a blaKPC-containing strain of K. pneumoniae belonging to the emergent lineage ST941, in order to better understand the evolution of blaKPC within this species.